The Asymptotics of Periodic Solutions of Autonomous Parabolic Equations with Rapidly Oscillating Coefficients and Equations with Large Diffusion Coefficients - S. A. Kashchenko; A. S. Polstyanov (Моделирование и анализ информационных систем, 2015)
We study the existence, structure and stability of periodic solutions of nonlinear systems referred to in the title.